2018
DOI: 10.1144/sp467.14
|View full text |Cite
|
Sign up to set email alerts
|

Martian gullies: a comprehensive review of observations, mechanisms and insights from Earth analogues

Abstract: Upon their discovery in 2000, martian gullies were hailed as the first proof of recent ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 325 publications
(564 reference statements)
0
14
1
Order By: Relevance
“…Does this suggest a role of water in the formation of martian gullies? Unfortunately, the findings reported in this paper do not provide any resolution to the ongoing debate between CO2 sublimation (e.g., Dundas et al, 2017, and references therein) and meltwater generation (e.g., Conway et al, 2018bConway et al, , 2018a, and references therein) for forming martian gullies. A meltwater hypothesis for this recent glacial erosion event on Mars leads to the reasonable assumption that gullies can be produced via a similar yet less widespread mechanism, which has been occurring periodically since this glacial erosion event.…”
Section: Gully-glacier Interactions On Marscontrasting
confidence: 62%
See 1 more Smart Citation
“…Does this suggest a role of water in the formation of martian gullies? Unfortunately, the findings reported in this paper do not provide any resolution to the ongoing debate between CO2 sublimation (e.g., Dundas et al, 2017, and references therein) and meltwater generation (e.g., Conway et al, 2018bConway et al, , 2018a, and references therein) for forming martian gullies. A meltwater hypothesis for this recent glacial erosion event on Mars leads to the reasonable assumption that gullies can be produced via a similar yet less widespread mechanism, which has been occurring periodically since this glacial erosion event.…”
Section: Gully-glacier Interactions On Marscontrasting
confidence: 62%
“…A meltwater hypothesis for this recent glacial erosion event on Mars leads to the reasonable assumption that gullies can be produced via a similar yet less widespread mechanism, which has been occurring periodically since this glacial erosion event. However, CO2 and H2O ices are often found together (Vincendon et al, 2010;e.g., Vincendon, 2015), and without more detailed knowledge on how CO2 sublimation might engender sediment transport assessing whether the morphological evidence fits with this transport mechanism remains difficult (Conway et al, 2018b).…”
Section: Gully-glacier Interactions On Marsmentioning
confidence: 99%
“…Mixing within the falling material will allow the generated heat to be transferred to the CO 2 frost, causing sublimation, enhancing the gas pressure within the pores of the flowing mass leading to fluidization of the flow. Complete fluidization is not necessary to explain all recent Martian gully flows, as the gully fans are moderately steep, roughly ranging between 10 • and 15 • (Conway & Balme, 2016;Gulick et al, 2019), and sometimes consistent with no fluidization (Kolb et al, 2010;Conway & Balme, 2016), and it is likely that a spectrum of behaviors occurs even within individual gullies (e.g., Conway et al, 2018b;De Haas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the formation of such ravine-like features formed in the absence of water has been renewed due to planetary studies. Numerous attempts to find terrestrial analogs for the gullies on Mars (see, for example, review by Conway et al 2019) showed that water-lacking processes (including ground ice melting) can produce only small gully-like features, which cannot be compared with large gully nets formed by water erosion. A general degradation of permafrost on the East European Plain with former periglacial conditions left numerous remnants of thermokarst features in recent relief morphology (Velichko 1965).…”
Section: Resultsmentioning
confidence: 99%